The role of village-owned enterprises (BUMDes) ‘Restu Ibu’ in community empowerment in Ngambon Village, Bojonegoro Regency - Oktaputri, Andini; Hidayat, Kliwon; Cahyono, Edi Dwi (Journal of Community Service and Empowerment, 2025)
BUMDes as a commercial organization established by the village government initiative based on the principles of deliberation, collaboration, community participation, transparency, empowerment, accountability, and sustainability. This study aims to analyze the roles and obstacles faced and describe the strategies of BUMDes managers in improving the development of Business Units in BUMDes Restu Ibu in Ngambon Village, Bojonegoro Regency. The data analysis method used consists of three flows consisting of data reduction, data presentation, conclusion drawing or verification. The results of the study show that BUMDes Blessing Ibu Ibu Ngambon Village in empowering the community still lacks community participation in advancing business units managed by BUMDes, lack of socialization related to BUMDes business units and institutional management which is still very poorly run. BUMDes management strategies in an effort to empower the community's economy through planning, organizing, mobilizing, and supervising activities. Village-Owned Enterprises (BUMDes) Restu Ibu is advised to encourage other members to work harder and the role of quality human resources to improve the quality of BUMDes in a more professional direction.